The Oprah Phenomenon - Watson, Elwood; Harris, Jennifer, 1971- (Book collections on Project MUSE., 2009)
Her image is iconic: Oprah Winfrey has built an empire on her ability to connect with and inspire her audience. No longer just a name, ""Oprah"" has become a brand representing the talk show host's unique style of self-actualizing individualism. The cultural and economic power wielded by Winfrey merits critical evaluation. The contributors to The Oprah Phenomenon examine the origins of her public image and its substantial influence on politics, entertainment, and popular opinion. Contributors address praise from her many supporters and weigh criticisms from her detractors. Winfrey's ability t.